Development Status and Trend of the Whole Process Engineering Consulting - Hanzheng Shi, Ruiling Zhang, Pengwen Xie (Forest Chemicals Review, 2022)
The global economy has entered an important period of digital transformation, all walks of life are in full swing, and the transformation and upgrading of traditional industries has been triggered. The whole process of development consulting is the embodiment of the industry’s implementation of the new development concept and the specific measures to implement the supply side structural reform in the consulting field. This paper analyzes the development status of the whole process engineering consulting industry, puts forward the research conclusions of the whole process engineering consulting trend, summarizes the existing problems in the development of the whole process engineering consulting industry. This paper suggested that the government issue binding measures, formulate technical standard system and management standard system to meet the needs of the whole process of engineering consulting services, and provide policy support for the whole process of consulting. The analysis results have guiding significance for the development of whole process engineering consulting in China. The whole process engineering consulting service will become the development trend of engineering consulting in the future with its advantages of integration, specialization and diversification.